USING LINEAR PROGRAMMING TECHNIQUE TO DETERME THE OPTIMAL COMODITY COMBINATION IN THE GENERAL COMPANY FOR FOOD PRODUCTS - VEGITABLE OIL FACTORIES (CASE STUDY) - & Al-Nassr, Al-Eqabi (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2021)
The objectives of the research are to determine the optimal allocation of resources available to the general company for food products using a linear programming(LP) technique to obtain high levels of production and high levels of profits by maximizing the value of the objective function and increasing the profitability of the company, and conducting a sensitivity analysis to see the extent of changes in the optimum commodity composition in terms of quality and quantity with the level of profits in a manner commensurate with the requirements of growth in the company , the study based on the use of (LP)technique to determine the optimum production plan with the highest net income for the products under study for vegetable oil factories as well as using sensitivity analysis by using the statistical program (Win QSB) .The research showed a number of results, perhaps the most important: proof of the hypothesis of achieving high levels of production and profits as well as the optimal allocation of available resources, as the quantity of production increased from 472 tons in the actual production plan to 974 tons in the derived plan , achieving a jump estimated at 106. 4%, and the results of the optimal solution using the (LP)technique showed that the value of net income at current prices has reached 348739500 dinars, an increase of 184.6% over the net income actually achieved at current prices of 122528565 dinars for the year 2018. The research had reached a number of conclusions, perhaps the most important is the matching of the research results to the research hypothesis as well as the optimal solution using the LP technique had showed the difference in the optimum commodity composition and its quantities from the actual commodity composition of the products , the research provides a number of recommendations, the most important of which is the application of a linear programming technique to know the extent of investing available resources in a way efficiency, which helps to increase production in order to achieve economic efficiency and the need to generalize it to production units with similar conditions in order to determine the optimal use of the various production resources.